An unusual finding of schwannoma in the columellar area—A case report. (2018) - Bouayyad, Sarah; Ong, Jen H.; Ellis, Matthew Peter; Sloan, Philip
Highlights: Schwannomas are rare in the sinosanal tract. We report the fourth case involving the columellar region. A large columellar schwannoma developed eight months into pregnancy. Pregnancy and young age seem to have a strong correlation with the lesion development. Open rhinoplasty offers a better approach to excise this kind of lesion. Abstract: Introduction: Schwannomas are benign tumours of the nerve sheath that originate from Schwann cells. Less than 4% of these tumours arise in the sinonasal tract. Columellar involvement is extremely rare – three other cases involving the columella have been reported since 1967. Presentation of case: A 25-year-old woman presented with a swelling of the nasal columella from eight months into pregnancy. She presented with right nasal obstruction and discomfort over the nasal bridge. Pre-operative MRI and ultrasound were performed. The mass was surgically excised using an external septorhinoplasty approach giving a good cosmetic outcome. Histopathologic examination demonstrated schwannoma. Discussion of case: Nasal schwannoma may present with variable symptoms. We discuss the MRI and histological features of schwannoma. A literature review suggests that schwannomas may have accelerated growth in pregnancy. The open rhinoplasty approach is the favoured method for excision of schwannomas near the columellar region. Conclusion: Nasal schwannomas are rare in the sinonasal tract, however they need to be considered part of the differential diagnosis for nasal masses. The treatment of choice for these lesions is surgical excision.